Integrating Science With Mathematics & Literacy : New Visions for Learning and Assessment. - Hammerman, Elizabeth (SAGE Publications, 2007)
Features tasks that model inquiry-based science and helps teachers evaluate learners' acquisition of complex thinking skills, aptitude for science, and ability to make real-world connections.